Role play in English language teaching - Calero Reyes, Reyna Violeta (2022)
Role Play in English allows these communication skills to be developed because it stimulates conversation, but also reading and listening comprehension. In addition to this, it offers the following advantages: Increases creativity. Role Play in English allows students to express themselves spontaneously and use their imagination to contextualize ideas and behaviors. • It's fun. With this technique, students can communicate with their peers in a relaxed and playful atmosphere, and this enjoyment leads to better learning. • Improves self-esteem. Many students are afraid to express themselves in English for fear of being wrong. With Role Play shyness is lost thanks to the relaxed atmosphere of the activity. An example of how efficient Role Play in English can be by putting menu conversations into practice in a restaurant. In this, students learn English through theatre, interpreting roles and learning their scripts in English. And once the program is completed, they can certify their level of English, which means that learning through this tool is effective. You will find a support for looking methodology in speaking skills and it might provide oral strategies like Role play, which has changed during the modern times in virtual and face to face classes. The first chapter is about Oral Competence in Peru, which concerns how Peru develops productive skills, the second chapter is about role play, its definition, its importance, and how it Works.